Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
1) \(x^2-x-y^2-y=\left(x^2-y^2\right)-\left(x+y\right)=\left(x-y\right)\left(x+y\right)-\left(x+y\right)=\left(x+y\right)\left(x-y-1\right)\)
\(x^2-2xy+y^2-z^2=\left(x-y\right)^2-z^2=\left(x-y-z\right)\left(x-y+z\right)\)
2)\(5x-5y+ax-ay=5\left(x-y\right)+a\left(x-y\right)=\left(x-y\right)\left(a+5\right)\)
\(a^3-a^2x-ay+xy=a^2\left(a-x\right)-y\left(a-x\right)=\left(a-x\right)\left(a^2-y\right)\)
a, x2-5xy+2x-10y = (x2 + 2x)-(5xy+10y)
= x(x+2)-5y(x+2)
= (x+2)(x-5y)
b, x2-5x+4 = x2- x - 4x +4
= (x2-x)-(4x-4)
=x(x-1)-4(x-4)
=(x-1)(x-4)
\(a,x^2-5xy+2x-10y\)
\(=\left(x^2-5xy\right)+\left(2x-10y\right)\)
\(=x\left(x-5y\right)+2\left(x-5y\right)\)
\(=\left(x-5y\right)\left(x+2\right)\)
\(b,x^2-5x+4\)
\(=x^2-4x-x+4\)
\(=x\left(x-4\right)-\left(x-4\right)\)
\(=\left(x-1\right)\left(x-4\right)\)
a,\(xy+3x-7y-21\)
\(=x\left(y+3\right)-7\left(y+3\right)\)
\(=\left(y+3\right)\left(x-7\right)\)
\(b,2xy-15-6x+5y\)
\(=\left(2xy-6x\right)+\left(-15+5y\right)\)
\(=2x\left(y-3\right)-5\left(3-y\right)\)
\(=2x\left(y-3\right)+5\left(y-3\right)\)
\(=\left(y-3\right)\left(2x+5\right)\)
a) x2 + 6x + 9 = x2 + 2 . x . 3 + 32 = (x + 3)2
b) 10x – 25 – x2 = -(-10x + 25 +x2) = -(25 – 10x + x2)
= -(52 – 2 . 5 . x – x2) = -(5 – x)2
c) 8x3 - 1/8 = (2x)3 – (1/2)3 = (2x - 1/2)[(2x)2 + 2x . 12 + (1/2)2]
= (2x - 1/2)(4x2 + x + 1/4)
d)1/25x2 – 64y2 = (1/5x)2(1/5x)2- (8y)2 = (1/5x + 8y)(1/5x - 8y)
4(x2+xy+xy+y2)+5x+=5y+1
=4(x2+xy+xy+y2)+4x+4y+x+y+1
=4(x2+xy+xy+y2+x+y)+(x+y+1)
=4(x+y)(x+y+1)+(x+y+1)
=(x+y+1)(4x+4y+1)
Hok tốt
\(4\left(x^2+2xy+y^2\right)+5x+5y+1\)
\(\Rightarrow4\left(x+y\right)^2+5\left(x+y\right)+1\)
\(\Rightarrow\left(x+y\right)\left[4\left(x+y\right)+5+1\right]\)
\(\Rightarrow\left(x+y\right)\left(4\left(x+y\right)+6\right)\)
\(\Rightarrow2\left(x+y\right)\left(2\left(x+y\right)+3\right)\)
a) \(x^2-xy+x-y\)
\(=\left(x^2-xy\right)+\left(x-y\right)\)
\(=x\left(x-y\right)+\left(x-y\right)\)
\(=\left(x+1\right)\left(x-1\right)\)
b) \(2xy-x^2-y^2+16\)
\(=16-\left(x^2-2xy+y^2\right)\)
\(=4^2-\left(x-y\right)^2\)
\(=\left(4-x+y\right)\left(4+x-y\right)\)
c) \(x^2-6x-16\)
\(=x^2-6x+9-25\)
\(=\left(x^2-6x+9\right)-25\)
\(=\left(x-3\right)^2-5^2\)
\(=\left(x-3-5\right)\left(x-3+5\right)\)
\(=\left(x-8\right)\left(x+2\right)\)
A) = xy(x3-y3)
= xy(x-y)(x2+xy+y2)
\(a,x^4y-xy^4\)
=> \(xy\left(x^3-y^3\right)\)
\(b,x^2-10y-5x-2xy\)
=> :))